Islamic Monetary Instruments Contribution to Economic Growth: Literature Study - Juliana Nasution; Andri Soemitra; Rifki Ismal; Amin Al Jawi; M.Indra Mulia Nasution; Afrizal Afrizal (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
In Islamic economics, the monetary sector and the real sector must be able to go side by side. Even the monetary sector must follow developments for the real sector. The goal of Islamic economics is the creation of economic justice through equitable distribution of income, one of which is seen from the growth of the real sector, which is a representation of the level of productivity and welfare of the community. This is directly related to the business world. Therefore, when the level of community productivity increases, it will aggregately affect economic growth. On the other hand, one of the monetary instruments in Islamic economics is Islamic banking. This means that the increasing performance of Islamic banking must be in line with the increase of the real sector. The purpose of this study is to analyze the contribution of increasing Islamic banking performance to economic growth through a literature study related to a qualitative approach, where the collected literature is analyzed by content analysis and the data is triangulated to make a conclusion. The findings of this study indicate that Islamic monetary instruments in the Islamic banking case contribute to economic growth through an increase from the real sector